Δυο επιστολές-υπόμνημα του Ελ.Βενιζέλου προς τον Ούινστον Τσώρτσιλ - Βερεμής Θάνος (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1983)
Greece’s involvement in Asia Minor forced the Greek government to contract three war loans from England in 1918, 1919 and 1920. After the Asia Minor disaster of 1922 the repayment of these loans added a further heavy burden on the strained resources of the country. The issue is raised in two letters-memoranda of 1925 and 1926 addressed by Eleftherios Yenizelos to Winston Churchill, then Chancellor of the Exchequer. In the memoranda Venizelos reminds Churchill of the responsibilities of Greece’s creditors for the Asia Minor campaign and disaster and attempts to persuade him to accept some modifications of her financial obligations. The two documents are published from the original drafts which survive in the Emmanuel Tsouderos Archive.